Characteristics of the Parameters of Somatic Construction and Fitness Level in Elderly People Based on Selected Fullerton Test Samples - Marek Zieliński; Jolanta Zielińska; Robert Ślusarz (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Aging should be understood, however, as a progressive deterioration of the function of organs and systems caused by the passage of time, which leads to a reduction of adaptability in stressful situations. The moment when deterioration of organ function starts, is individually variable, just as the pace of its progress. Linking physical fitness with health is known as the H-R-F (Health-Related Fitness) concept. It corresponds to those components of fitness, which result from both the beneficial and adverse effects of regular physical activity, and which are related to the level of health condition. Aim. The purpose of this study is to present the results of research on basic somatic construction parameters and of selected physical fitness tests of the students of Kujawsko-Dobrzyński Third Age University of the University of Humanities and Economics in Wloclawek, aged over 60. Material and Methods. The research material consists of the data obtained from somatic measurements and fitness tests conducted among students of Kujawsko-Dobrzyński University of the Third Age at the University of Humanities and Economics in Wloclawek. Cross-sectional research was carried out under UHE team grant in November 2014 among 30 women. The age of the female students ranged from 60 to 75 years with the average age of 65 years. The group of women included in the tests were attending classes at the University of the Third Age at the University of Humanities and Economics, undertaking activities related to physical activity of elderly people in the area of a physical recreation (15 women) and the ‘solo’ dance (15 women). The classes of widely understood physical activity were supplemented by lectures and seminars in the field of philosophy, pedagogy, gerontology and life sciences. Results. The study showed that the average age of the students was 65 years, the average value of the body weight was below 70.9 kg, and the average body height was 159.7 cm. Body mass index in more than 63% of women can be classified into the category of overweight and only in the case of 17% of the respondents the index can be regarded as standard. The analysis of physical fitness indicates that the average value of the strength of the upper limbs in an attempt to bend the forearm exceeds 22 repetitions, and the mean strength of the lower limbs in an attempt to stand up from a chair is 19.13 repetitions. Conclusions. 1. The age of the study groups is different (a statistically significant difference) whereas the BMI index is the same. 2. In both fitness tests better results (statistically significant) were obtained by female listeners participating in fitness classes, which may result from the increased physical activity of higher intensity and frequency. (JNNN 2015;4(2):48–55)